Kompetensi dan Motivasi Sumber Daya Manusia dalam Pembelajaran - Juhra, Al (Pencerah, 2024)
The human resources issue remains the focus and focus of an organization's ability to survive in the age of globalization. Human resources will determine the success of the organization's activities. This research aims to find out how the competence and motivation of human resources in learning. This analysis uses qualitative methods with descriptive approaches, data collection obtained through observations, interviews, and documentation. Determination of informants using purposive sampling techniques, then once research data is collected then analyzed using data analysis techniques. The results of the research show that the improvement in the quality of individual and organizational performance will occur in a learning organization that is able to combine leadership functions, managers' competencies and cultures that enable the competence to develop and be used optimally in the form of a continuous innovation contribution in the organization.